Neural correlates of emotion-attention interactions: From perception, learning, and memory to social cognition, individual differences, and training interventions. (January 2020) - Dolcos, Florin; Katsumi, Yuta; Moore, Matthew; Berggren, Nick; de Gelder, Beatrice; Derakshan, Nazanin; Hamm, Alfons O.; Koster, Ernst H.W.; Ladouceur, Cecile D.; Okon-Singer, Hadas; Pegna, Alan J.; Richter, Thalia; et al.
Highlights: Emotion-attention interactions impact many aspects of daily life. These interactions involve interplays between affective and executive brain systems. Individual differences (age, sex, personality) can modulate emotion and attention. Maladaptive emotion-attention interactions are common in affective disorders. Training and interventions can optimize emotion-attention interactions. Abstract: Due to their ability to capture attention, emotional stimuli tend to benefit from enhanced perceptual processing, which can be helpful when such stimuli are task-relevant but hindering when they are task-irrelevant. Altered emotion-attention interactions have been associated with symptoms of affective disturbances, and emerging research focuses on improving emotion-attention interactions to prevent or treat affective disorders. In line with the Human Affectome Project's emphasis on linguistic components, we also analyzed the language used to describe attention-related aspects of emotion, and highlighted terms related to domains such as conscious awareness, motivational effects of attention, social attention, and emotion regulation. These terms were discussed within a broader review of available evidence regarding the neural correlates of (1) Emotion-Attention Interactions in Perception, (2) Emotion-Attention Interactions in Learning and Memory, (3) Individual Differences in Emotion-Attention Interactions, and (4) Training and Interventions to Optimize Emotion-Attention Interactions . This comprehensive approach enabled an integrative overview of the current knowledge regarding the mechanisms of emotion-attention interactions at multiple levels of analysis, and identification of emerging directions for future investigations.